A SECURE VIDEO STEGANOGRAPHY TECHNIQUE BASED ON MOTION DETECTION - Kaur, Karamjit; Laxmi, Vijay (International Journal of Computer Sciences and Engineering, 2025)
Steganography is a sort of cryptography in which the mystery message is covered up in an advanced picture. While cryptography is engrossed with the security of the substance of a message or data, Steganography focuses on hiding the specific presence of such messages from recognition. In the proposed system, maximum motion and high intensity between every consecutive frame is evaluated. The frame must be found in which maximum motion and intensity is there and this frame is marked as the target frame. This technique provides a large amount of security to the stego video as it is very difficult for the attacker to guess or find the target frame in which secret message is hidden. The proposed system hides the image in video frames that is indistinguishable. Video is collection of frames that contains multiple redundancies which provide high security to transfer data from one location to another. Video steganography gives emphasis on hiding the data in such a way so that it cannot be even detected by naked eyes. The unauthorized person may conceal data that is travel from one location to another location .A secure method is needed to safe information from unauthorized person. In the proposed work, Least Significant Bit (LSB) along with motion estimation is used to hide the message into a video in such way that does not raise suspicion. The proposed system generates the better results in terms of PSNR, MSE as compared to existing system